KEMEMPANAN ISOLAT LOKAL NEMATODA ENTOMOPATOGEN Steinernema carpocapsae Poinar UNTUK PENGENDALIAN HAMA ULAT GRAYAK (Spodoptera litura F.) PADA TANAMAN KUBIS EFFICACY OF Steinernema carpocapsae Poinar ENTOMOPATHOGENIC NEMATODE LOCAL ISOLATE TO CONTROL ARMY WORM (Spodoptera litura F.) ON CABBAGE CROP - Mana, Abdul; Suyanto, Agus (Pembangunan Pedesaan, 2009)
Research studying efficacy of Steinernema carpocapsae entomopathogenic nematode local isolate against army worm (Spodoptera litura F.) was conducted in the Laboratory of Plant Nematology, the Departement of Plant Pests and Deseases, Agriculture Faculty, Jenderal Soedirman University, Purwokerto. Both the efficacy test of S. carpocapsae against S. litura and the effect test of S. carpocapsae on S. litura development were designed by Split Plot Design based on Randomized Complete Block Design. Treatments tested were the origin of isolates, i.e., Cilacap and Brebes, and several invective juvenile nematode concentrations. Variables observed were larval mortality and numbers of pupae, adults, eggs, and hatched eggs. Results of the reserach showed that both local entomopathogenic nematode had low efficacy on S. litura, i.e., larval mortality for Cilacap and Brebes isolates of 25.5 and 28.2%, respectively. LC50 of Cilacap and Brebes isolates was 1,695.36 and 1,908.31 nematode ml . The local isolate nematodes could not inhibit S. litura development.